Economic Offenses in the Field of Road Safety in the Practice of The Commercial Court in Valjevo - Obradović, Dragan; Karać, Stevan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2021)
In addition to criminal acts and misdemeanors, in the field of road traffic safety, there are also economic offenses, a specific type of criminal offenses. In this paper, we have pointed out certain characteristics of economic crimes and certain problems in their application today. We focused on the transport of cargo, given its importance for business, as well as economic offenses in this regard. We presented certain data of importance for this issue in Serbia and the area of the Commercial Court in Valjevo. Our goal is to harmonize the work of the police and the judiciary in the area where the jurisdiction of the Commercial Court in Valjevo and Serbia extends, through the problems we have identified and pointed out. This is necessary in order to act more efficiently of all competent state bodies in this specific area of the fight against irresponsible legal entities and responsible persons in legal entities that organize work on the transport of goods within the scope of their activities.